Understanding networks in low-and middle-income countries’ health systems: a scoping review - Kalaris, K; Wong, G; English, M (Public Library of Science, 2023)
Networks are an often-employed approach to improve problems of poor service delivery and quality of care in sub-optimally functioning health systems. There are many types of health system networks reported in the literature and despite differences, there are identifiable common characteristics, uses, purposes, and stakeholders. This scoping review systematically searched the literature on networks in health systems to map the different types of networks to develop an understanding of what they are, when and what they are used for, and the purposes they intend to achieve. Peer-reviewed literature was systematically searched from six databases (Medline (Ovid), EMBASE (Ovid), Global Health (Ovid), the Cochrane Library, Web of Science Core Collection, Global Index Medicus’s Africa Index Medicus) and grey literature was purposively searched. Data from the selected literature on network definitions, characteristics, stakeholders, uses, and purposes were charted. Drawing on existing frameworks and refining with the selected literature, a five-component framework (form and structure, governance and leadership, mode of functioning, resources, and communication), broadly characterizing a network, is proposed. The framework and mapping of uses, purposes, and stakeholders is a first step towards further understanding what networks are, when and what they are used for, and the purposes they intend to achieve in health systems.